Features of laboratory control under conditions of functioning of institutions for children (Environment & Health, 2020)
Objective: We determined a list of the objective research methods for assessing the sanitary and epidemiological welfare of institutions for children in the context of reforming the medical and educational systems in Ukraine.Materials and methods: A range of issues and research methods in child institutions of various types, regarding their sanitary and epidemiological welfare was determined on the basis of the analysis of scientific literature, evaluation of laboratory research results on the functioning conditions of child institutions conducted by the regional laboratory centers of Ukraine, data of the State Statistics Committee of Ukraine, own research in 2018-2019.Results: Taking into account the processes of the reform of medical and educational systems in Ukraine, the issues of sanitary-chemical, sanitary-bacteriological, physical research and assessment of the risk from economic activities of child institutions: nutrition safety; anti-epidemic measures of the occurrence and spread of infectious diseases; the quality of air environment and child household items; lighting and microclimate in the main premises for children’s stay; the presence of noise and vibration factor, electromagnetic radiation (EMR); organization of training process; indicators of the health of children remain relevant.Conclusions: Nowadays, the identification of the risk factors for child health during their education should be underlined. The inconsistency of state control between different departments leads to a violation of the healthy conditions for vital activity of the large groups of children, a deterioration of the material and technical equipment of the laboratory base and a decrease in the professional competencies of the specialists of laboratory medicine.
Keywords: health status of children; institutions for children; sanitary and epidemiological welfare; methods of state control